Abraham's ashes the absurdity of monotheism - Heinegg, Peter (Lanham, Md. : University Press of America, 2013)
"Abrahamic religion has long been a buzzword in ecumenical discourse. It is the notion that Judaism, Christianity, and Islam, despite their profound differences, are united in their reverence for Abraham -- not just as the progenitor of Israel, but as a universal father in the faith. Abraham's Ashes offers a forceful critique of the biblical and Qur'anic views of Abraham, showing how at the heart of all prophetic religions lies an untenable myth of suprarational magical thinking about "revelation." This myth involves communiqués to a privileged male from a mysterious patriarchal God who demands, and in the case of Jesus, actually receives the tribute of human sacrifice. This cruel story proves to be an apt introduction to the bizarre, contradictory, and oppressive fantasy known as monotheism"--Book cover.
Introduction : crazy Abe -- A bad beginning -- The son who was sacrificed -- Abraham, the first Muslim -- Conclusion : farewell to the lunacy.
Description based on print version record.
Keywords: Monotheism; Abraham (Biblical patriarch) in the New Testament; Abraham -- (Biblical patriarch) -- In the Koran; Abraham -- (Biblical patriarch) -- In rabbinical literature; RELIGION / Theism; Electronic books